PENGARUH PERKEMBANGAN USAHA MIKRO KECIL MENENGAH (UMKM) TERHADAP PERTUM-BUHAN EKONOMI DI JAWA TIMUR - Dewi, Bunga Aksana; Suprapto, Eddy (Journal of Development Economic and Social Studies, 2022)
This study aims to determine the effect of micro, small and medium enterprises (MSMEs) on economic growth before the COVID-19 pandemic in 2018- 2019 and after the Covid-19 pandemic in 2020-2021, where MSMEs are the largest contributor to GRDP in East Java. This type of research is quantitative using time series data which is secondary data obtained from BPS and the Department of Cooperatives and SMEs. This study uses the research method panel data analysis with independent variables, namely the number of SMEs, the number of workers and the dependent variable is GRDP. From the partial test, it is found that the MSME growth variable has a positive and significant effect on economic growth while the variable number of workers is not significant on economic growth.